The genus Stevia (Eupatorieae, Asteraceae) in Chile: a taxonomical and morphological analysis - Gutiérrez, Diego G.; Muñoz-Schick, Mélica; Grossi, Mariana A.; Rodríguez-Cravero, Juan F.; Morales, Vanezza; Moreira-Muñoz, Andrés (Phytotaxa, 2016)
A taxonomical study of the Chilean Stevia is herein presented since there is no agreement on current names and the number of species for Chile. A detailed morphological analysis of type and non-type specimens including new field observations was undertaken. In this work we recognized only one species of Stevia in Chile: S. philippiana. This species has a wide morphological variation mainly in leaf and pappus features. A lectotype of the name S. hyssopifolia was designated. Stevia hyssopifolia var. panulensis was regarded as a new synonym of S. philippiana. On the other hand, S. adenophora and S. chamaedrys were excluded from the Chilean flora. Finally, Porophyllym tarapacanum was excluded from the Tagetean genus Porophyllum and included as a new synonym of S. philippiana, too.